Circuit Compatibility for Retired Quantum Systems - Marek WRÓBLEWSKI; Marek SAWERWAIN (Communications of International Proceedings, 2024)
The article presents the consequences and implications of the development of quantum computing technologies in the context of designing circuits based on quantum gates, which are mechanisms for artificial intelligence algorithms. The main motive behind this article is to indicate the possibility of adapting currently existing quantum applications and circuits created on their basis using the Qiskit framework to currently available IBM Q quantum platforms. The differences in code implementations are so significant that they should be explicitly indicated in the chapters below, so that it would be possible to adapt and develop existing algorithmic solutions in modern quantum platforms. When conducting the latest literature review, it is noted that there is no explicit indication of how to proceed in the case of performing circuit adaptation in order to further develop current quantum solutions and later run them in the IBM Q quantum environment. For this purpose, methodologies from the field of software engineering, including quantum engineering, and characteristics of the area of revers engineering were used, with the aim of developing a method enabling circuit adaptation for retired hardware quantum architectures. The dynamism of the development of quantum computer platforms necessitates the adaptation of originally programmed quantum artificial intelligence methods using quantum circuits to the currently available quantum hardware environment.
Keywords: recommendation mechanism; quantum computing; quantum circuit; implementation algorithm; machine learning; transpiling; circuit adaptation; backward compatibility